Development of interactive Powtoon Multimedia to Improve Elementary Students’ Cognitive Learning Outcomes - SEVTI ELLY FIA NUR ANGGRAENI; Agustin, Ina (Jurnal Gentala Pendidikan Dasar, 2025)
This research aims to develop an interactive multimedia product based on Powtoon to improve the cognitive learning outcomes of elementary school students. The background of the study stems from the low cognitive performance of students due to the limited use of innovative learning media, especially in thematic subjects such as IPAS. This research employed the ADDIE development model. The study was conducted in a third-grade class at UPT SD Negeri Kapu 2, Tuban, involving media validation by experts, practical usage trials with teachers and students, and cognitive effectiveness testing through pretest and posttest. The validation results from media, material, and language experts indicated high levels of validity with scores of 97.8%, 88%, and 96.7%, respectively. Practicality was evaluated through teacher and student questionnaires, yielding scores of 94% and 99.2%. The effectiveness test based on N-Gain analysis showed a gain score of 0.69, categorized as moderately effective. These results indicate that Powtoon-based multimedia is highly valid, practical, and sufficiently effective in enhancing students’ cognitive learning outcomes. It is recommended as an alternative instructional media to create engaging and interactive learning experiences in elementary education.